(untitled) (Nigerian Journal of Physiological Sciences, 2024)
The development of cardiovascular diseases and type 2 diabetes is preceded by the risk factors of metabolic syndrome (MS) which are often induced by high-carbohydrate high-fat diet (HCHFD) together with sedentary lifestyle. These risk factors are associated with vascular dysfunction. Our previous study has shown that ursolic acid (UA) prevents the development of these risk factors of MS induced by HCHFD, but the potential mechanism involved in the amelioration of vascular dysfunction induced by HCHFD has not been explained. This study investigated the mechanism by which dietary UA supplementation improves vascular dysfunction and the corresponding vascular oxidative stress in male Wistar rats fed a HCHFD. Twenty (20) male Wistar rats were randomly divided into 4 groups (n =5): 1- normal diet (ND) + distilled water (DW); 2 – ND+UA; 3 – HCHFD+DW; 4 – HCHFD+UA. HCHFD was formulated in-house. The animals were fed their respective diets daily for 20 weeks. The drinking water of animals fed a HCHFD was augmented with 20% fructose. 250 mg/kg body weight of ursolic acid was administered orally to UA-treated groups for the last 8 weeks of the study. Body mass index (BMI) and abdominal circumference were evaluated; serum insulin and nitric oxide were assessed by using enzyme-linked immunosorbent assay kits; and insulin resistance was determined using the homeostatic model assessment for insulin resistance (HOMA-IR). Aortic antioxidant enzymes and reactive oxygen species were evaluated. Aorta and adipose tissues’ endothelial nitric oxide synthase (eNOS) was evaluated using real-time polymerase chain reaction technique. There was a significantly (P<0.05) lowered BMI percentage increase in the HCHFD+UA-fed animals compared to the HCHFD+DW-fed animals. In the HCHFD+UA-fed animals, serum insulin and HOMA-IR were significantly (P<0.05) decreased compared to the HCHFD+DW-fed animals. Serum nitric oxide was significantly (P<0.05) increased in HCHFD+UA-fed animals compared to the HCHFD+DW-fed animals. In HCHFD+UA-fed animals, aorta superoxide dismutase, catalase and glutathione were significantly (P<0.05) increased, compared to the HCHFD+DW-fed animals. Aorta reactive oxygen species was significantly (P<0.05) decreased in HCHFD+UA-fed animals compared to the HCHFD+DW-fed animals. Both aorta and adipose tissue eNOS mRNA level was significantly (P<0.05) more expressed in the HCHFD+UA-fed animals compared to the HCHFD+DW-fed animals. Findings from this study showed that ursolic acid supplementation ameliorates vascular dysfunction by upregulating eNOS gene in male Wistar rats with high-carbohydrate high-fat diet (HCHFD)-induced metabolic syndrome